Dampak Lingkungan Hidup Dalam Pemberian Persetujuan Lingkungan - Koedoeboen, Yeremia Puja Hua; Pietersz, Jemmy Jefry; Saija, Vica Jillyan Edsti (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: One of the important instruments in environmental management is permits. Licensing in an environmental context is referred to as an environmental permit. Environmental permits are understood as an important element in efforts to control activities and/or businesses so that the environment does not suffer a detrimental impact. In order to fulfill administrative activities to obtain environmental approval, there are documents that must be fulfilled, namely, AMDAL or UKL -UPL. After fulfilling one of these conditions, an environmental permit will be issued by the Minister, Governor, or Regent/Mayor in accordance with their authority by including the requirements contained in the environmental feasibility decision document or UKL-UPL recommendation. The research method used in this writing uses normative juridical research, where this type of research is analytical. The sources of legal materials used are primary and secondary legal materials. The collection technique is through literature study and then analyzed through descriptive methods. To obtain environmental approval, there are several conditions that must be met, one of which is through the ANDAL and RKL-RPL addendum. ANDAL is used as a careful assessment of the impact of an activity. ANDAL aims to analyze an activity that has the potential to have an impact on the environment, which will also become an important point in making decisions regarding permits for an activity. So it can be concluded that ANDAL is also the most important part of granting environmental approval.